Weight changes from early to middle adulthood and cardiometabolic multimorbidity later in life among middle-aged and older adults: a retrospective cohort study from the NHANES 1999-2018 - Zhao, Fayun; Zhao, Qiang; Wang, Huandong; Wang, Kun; Kong, Shenke; Ma, Peiyao; Wang, Xin (Frontiers in Endocrinology, 2024)
Background Weight gain in adulthood can influence the development of diabetes and cardiovascular diseases. It is speculated that weight gain is related to cardiometabolic multimorbility (CMM). This study was designed to examine the relationships between weight changes from early to middle adulthood and the risk of CMM.Data of the National Health and Nutrition Examination Survey (NHANES) 1999-2018 cycles were analyzed in the present study. Weights at age 25 years and 10 years before recruitment were self-reported and were used to define five weight change patterns including stable normal, maximum overweight, obesity to non-obesity, nonobesity to obesity, and stable obesity patterns. Meanwhile, absolute weight changes were classified into five groups: weight loss≥ 2.5 kg, weight change within 2.5 kg, 2.5 kg≤ weight gain < 10.0 kg, 10.0 kg≤ weight gain < 20.0 kg, and weight gain≥ 20.0 kg. CMM was defined as the coexistence of two or three of diabetes, coronary heart disease (CHD), and stroke.Results A total of 25994 participants were included. Across adulthood, compared to stable normal weight, maximal overweight, obesity to non-obesity, non-obesity to obesity, and stable obesity were consistently associated with increased risks of diabetes, CHD, and CMM. For instance, stable obesity was respectively related to 357358.60% (HR: 4.57658, 95% CI: 4.573, 4.57958), 88.0% (HR: 1.880, 95% CI: 1.878, 1.882), and 291292.90% (HR: 3.91992, 95% CI: 3.914, 3.924) higher risks of diabetes, CHD, and CMM. Meanwhile, any account of weight loss and gain was linked to higher risks of diabetes, CHD, and CMM than weight change within 2.5 kg. However, participants with maximum overweight had a decreased incidence of stroke (HR: 0.854, 95% CI: 0.853, 0.85586), and weight loss ≥ 2.5 kg and weight gain ≥ 2.5 and <20 kg were also related to a lower risk of stroke. J shaped or U shaped associations of absolute weight changes with the risks of diabetes, CHD, and CMM were observed.Conclusions Maintaining a stable normal weight can benefit more from the prevention of diabetes, CHD, and CMM. Both weight gain and loss across adulthood were accompanied by increased risks of diabetes, CHD, and CMM.